Instructional competence of public secondary school teachers in the district of Naic: Basis for instructional enhancement program - Mae N. Asis, Johanna; G. Caballes, Dennis; E. Ortiz Jr., Oliver (Polaris Global Journal of Scholarly Research and Trends, 2023)
The study aimed to determine the level of instructional competence of Public Secondary School Teachers in the District of Naic in formulating an instructional enhancement program. Likewise, the teachers' profiles were also examined as part of the investigation. To achieve this goal, the researcher conducted a study to determine the level of instructional competence in terms of instructional delivery, assessment, classroom management, and personal competencies (skills) among public secondary high schools in the District of Naic, Cavite. In this manner, the non-experimental descriptive method was used to measure teachers' degrees of instructional competence. A qualitative design was also utilized to identify the problems met by the respondents. A total of 100 teachers who are currently employed in the public secondary schools in Naic were involved in this study using purposive sampling. Moreover, the information for the study was gathered using a valid and reliable researcher-made questionnaire. The results revealed that the instructional competencies among teachers are highly competent. The result on the significant difference of instructional competence against profile variables of teachers revealed no significant difference. Ultimately, an instructional enhancement program was proposed to improve instructional competence in addressing the problems met by public secondary school teachers.